4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:06:11
4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x&
4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x
4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x
4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x
0.3分之3x-1=0.6分之4-x +0.2分之3x+5
4分之5x-0.3=0.6分之3x-1.2+1.2分之1.8-6x
0.6分之1.1-4x-0.2分之1.3-3x=0.3分之5x-0.4
0.6x+5分之2x-7分之3x=3分之4解方程
4分之x+3=x-5分之x-1
4分之x+3=x-5分之x-1
3分之0.6=x分之2x分之7=5分之0.5 4分之x=0.1分之1
0.3分之2x-0.6分之1.6x-3x=3分之31x+8
解方程.x-2分之1=4分之3,x+8分之7=4分之5,x-15分之14=2分之1.
X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
X分之40=3分之60 2.4:5=X:2分之7 4分之1.2=X分之0.6 1.75:0.35=1.2分之X 16分之5:4分之1=X:3.2 解比例
5分之x+4-(x-5)=3分之x+3-2分之x-2
5分之(X+4)-(X-5)=3分之(X+3)-2分之(X-2)
2分之x-4分之3-4x=2-x-8分之5-3x
5分之x+4-(x-50)=3分之x+3-2分之x-2
2分之x+4-x+5=3分之x+3-6分之x-2
2分之5=4分之(x+3)-0.8分之(0.2-0.3x)
x+5分之2=x分之1 x-4分之x-1=x-4分之3 2